Penampilan Watak Tokoh dalam Cerkak â€œDidongakne Malah Nesuâ€ Karya Djaid Belor - Safarina, Reny Anindhita; Sulanjari, Bambang; Werdiningsih, Yuli Kurniati (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2023)
The purpose of writing this scientific paper is to fulfill lecture assignments in order to develop writing skills and describe a person's character based on interactions between characters in a short story literary work or it can also be called cerkak. The story comes from a Javanese-language magazine published in 2019. However, what will be discussed in this scientific paper is the one with the title Didongake Malah Nesu which was created by Djaid Belor. The method used in this research is qualitative. Research data in the form of cerkak texts sourced from Javanese-language magazines published in 2019 tells of the reality of a husband and wife as officials who were accidentally prayed for by foreigners. The theory used is literary psychology that focuses on the behavior of characters that clearly describe the character's character. The results of this study are to find out the inner conflict that occurs in each character, to know the psychological condition of the character and the psychology of the author through the plot of the short story. Each character has a different role and response to the events they face to make the story interesting. This behavior becomes a reference for knowing the character's character through conversations and interactions between characters.